ОСОБЕННОСТИ АНОЗОГНОЗИИ ПРИ СИНДРОМЕ ЗАВИСИМОСТИ ОТ ПСИХОСТИМУЛЯТОРОВ - Грановская, Елизавета Александровна; Бочаров, Виктор Викторович; Шишкова, Александра Михайловна; Рыбакова, Юлия Валерьевна; Илюк, Руслан Дмитриевич (Медицина: теория и практика, 2020)